1998
DOI: 10.1590/s0100-879x1998001100013
|View full text |Cite
|
Sign up to set email alerts
|

Decreased spermatogenic and androgenic testicular functions in adult rats submitted to immobilization-induced stress from prepuberty

Abstract: We investigated whether chronic stress applied from prepuberty to full sexual maturity interferes with spermatogenic and androgenic testicular functions. Male Wistar rats (40 days old) were immobilized 6 h a day for 60 days. Following immobilization, plasma concentrations of corticosterone and prolactin increased 135% and 48%, respectively, while plasma luteinizing hormone and testosterone presented a significant decrease of 29% and 37%, respectively. Plasma concentration of follicle-stimulating hormone was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 20 publications
3
28
2
1
Order By: Relevance
“…The authors hypothesized that the increase in testicular apoptosis was the result of decline of gonadotropins and subsequently testosterone hormonal level that influenced the testicular cellular viability [37] Citation: Lasheen SS, Refaat SH, EI-Nefiawy NE, Abd-Elgawad RA, Othman AI, et al found that testosterone replacement at birth in offspring males exposed to prenatal stress was able to reverse changes in sexual behavior. Numerous studies also found increase in number of apoptotic cells in spermatogenic epithelium after exposure of adult rats to chronic stress [38][39][40][41] suggested that high levels of cortisol, the stress hormone, in the blood is the reason for germ cell apoptosis as glucocorticoids control mitosis and apoptosis induction of the germinal epithelium. Interestingly, apoptosis was seen to occur in a developmental stagespecific manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors hypothesized that the increase in testicular apoptosis was the result of decline of gonadotropins and subsequently testosterone hormonal level that influenced the testicular cellular viability [37] Citation: Lasheen SS, Refaat SH, EI-Nefiawy NE, Abd-Elgawad RA, Othman AI, et al found that testosterone replacement at birth in offspring males exposed to prenatal stress was able to reverse changes in sexual behavior. Numerous studies also found increase in number of apoptotic cells in spermatogenic epithelium after exposure of adult rats to chronic stress [38][39][40][41] suggested that high levels of cortisol, the stress hormone, in the blood is the reason for germ cell apoptosis as glucocorticoids control mitosis and apoptosis induction of the germinal epithelium. Interestingly, apoptosis was seen to occur in a developmental stagespecific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Weight, length and width of the testes and height of germinal epithelium were remarkably decreased. Other group found reduction in spermatid count in rats subjected to immobilization stress during prepubertal period and left to be assessed when reached adulthood [41].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged immobilization caused no significant change in plasma FSH but induced a significant delay in testicular maturation, in addition to a decrease in spermatid production and in sperm density in both pubertal and adult animals (3,4). Few literature data pertaining to stress and sexual behavior have shown that prenatal (6) or neonatal (7,8) stimulation may impair the copulatory performance of both male and female adult rats.…”
Section: Introductionmentioning
confidence: 98%
“…(1) erectile dysfunction (Nathan, 1986;Ernst et al, 1993;Kennedy et al, 1999), (2) decrease of sperm quality (Almeida et al, 1998;Clarke et al, 1999;Hari Priya and Sreenivasula Reddy, 2012;Hari Priya et al, 2014;Rao et al, 2015;Zhang et al, 2015), (3) decrease of testosterone levels (Orr and Mann, 1990;Retana-Márquez et al, 2003;Weissman et al, 2009;Lin et al, 2014;Prabsattroo et al, 2015), and (4) damage to testicular tissue (Rai et al, 2003;Aziz et al, 2013;Prabsattroo et al, 2015). Indeed, the corticosterone levels are markedly elevated under a restraint immobilization condition (Bhatia et al, 2011;Prabsattroo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%